Panorama do trabalho rural na cafeicultura de montanha (Revista de História Regional, 2025)
The article configures rural work in the panorama of coffee agribusiness in the south of Minas Gerais. Mountain coffee farming accounts for more than 32% of national Arabica coffee production and presents a production dynamic strongly linked to the interests of the international market. Considering the topographic obstacles to mechanization, the high density of work stands out, especially in the harvesting operation, with regimentation, in large-scale and employer-based coffee farming, with a large contingent of temporary workers, the pickers. In the field of labor relations, informality, precariousness, itinerancy, intermittency and vulnerability predominate, with repeated accusations and evidence of work relations analogous to slavery. Based on specific and regional bibliography, the text presents three sections, in addition to the introduction and conclusion: firstly, it presents explanatory information on the spatialization of coffee production and the characterization of the productive zone in the South of Minas Gerais; Next, it focuses on the configuration of rural work in local coffee farming and; subsequently, it pays attention to the occurrence of work similar to slavery and recurrence to migrant workers.
Keywords: Coffee farming; Informality; Migrant; Minas Gerais; Rural worker